Pelatihan Kesehatan Keselamatan Kerja dalam Menunjang Kegiatan Produksi di Ilham Meubel - Wijayanti, Rahma Rina; Ardhiarisca, Oryza; Fitri, Zilvanhisna Emka; Avisenna Harkat; Kholiq, M. Avan Dwi Adi Nur; Muhammad Hanip; Ubaidillah, Yanuar Ardhika Rahmadhani (Politeknik Negeri Jember, 2025)
lham Meubel is a wood craftsman who produces various products including: tables, chairs, frames, doors, sideboards, kitchen sets and so on. The problems faced by partners when running a business are that the production equipment they have is no longer suitable, namely a serkel table that is outdated and they don't have a nail gun that is needed to support activities when installing products for clients from Ilham Meubel. Apart from that, craftsmen do not prioritize occupational health and safety (K3). This can be seen when working partners do not wear any K3 equipment during their activities. Therefore, in this service activity, solutions will be provided regarding these problems which will be carried out in stages, namely eight months. The first solution given was the provision of serkel tables and nail guns and the next was the provision of K3 equipment along with training. The target of this service activity is to improve production quality accompanied by the use of K3. The output of this service is a service journal, online mass media articles and videos of activity implementation